Applying experiences with declarative codifications of software architectures on cod - Wuyts, Roel; Ducasse, Stéphane; Arévalo, Gabriela Beatriz (2001)
This position paper presents some preliminary work we made for applying declaractive component oriented design in the context of embedded devices. We quickly describes COMES the model we develop and present how logic rules can be used to describe architectures.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Workshop on Component Oriented Programming (ECOOP). (6º : 2001 : Budapest, Hungría)
Keywords: DESARROLLO DE MODELOS; ARQUITECTURA DE SOFTWARE